Imports, Exports and Foreign Reserves in Nigeria: Exploring the Long and Short-Run Relationships from the Vector Error Correction Model (VECM) Approach - Echobu, John; Kighir, Emmanuel Apedzan; Odunko, Stella Nonyelum (FUDMA Journal of Accounting and Finance Research [FUJAFR], 2024)
The imports of goods and services, a component of international trade, can boost economic progress when carried out on productive commodities. However, excessive imports of goods and services also stifle the growth of indigenous industries. Understanding the short- and long-run relationships between imports and other macroeconomic factors is necessary for planning by managers of the economy. This study examined the relationship between imports, exports, and foreign reserves in Nigeria for 10 years spanning from 2012 to 2021. Monthly time series data were tested for stationarity using the augmented Dickey-Fuller test, which showed that all the variables were integrated at order I (1). The Johansen co-integration test showed a stable long-run relationship between imports, exports, and foreign reserves. The regression estimates from the vector error correction model showed a long-run causal relationship (negative) between imports, exports, and foreign reserves. Furthermore, the foreign reserve has a significant short-run causal relationship with imports. Exports did not show any short-run causal relationship with imports. Both imports and foreign reserves do not have any causal relationship with exports in the short run. However, an insignificant causal relationship exists in the short run between exports and foreign reserves, while imports do not have any causal relationship with foreign reserves. The study recommends an optimum level of foreign reserve, which can be used to check the tendency of excessive importation, which is detrimental to the growth of local industries.
Keywords: Import; Export; Foreign Reserves; Vector Error Correction Model